CRUSTAL STRUCTURE IN THE CARPATHO-PANNONIAN REGION: INSIGHTS FROM THREE-DIMENSIONAL GRAVITY MODELLING AND THEIR GEODYNAMIC SIGNIFICANCE - Szafián P.; Horváth F. (My University, 2006)
A three-dimensional gravity modelling of the Carpatho-Pannonian region was carried out to get a better image of the Moho boundary and the most prominent intra-crustal density heterogeneities. At first, only the major density boundaries were considered: the bottom of the Tertiary basin fill, the Moho discontinuity and the lithosphere to asthenosphere boundary. Density contrasts were represented by relative densities. The improved density model shows a transitional unit of high density at the base of the crust along the Teisseyre-Tornquist Zone. In the Western Carpathians, an extensive, relatively low-density unit was inferred in mid-crustal levels. The border zone between the Southern Carpathians and the Transylvanian basin is characterized by a sharp, step-like contact of the two crustal units. The Moho configuration reveals important information on the tectonic evolution of the region. Zones of continental collision are represented by thick Moho roots (Eastern Alps, Eastern Carpathians). Transpressional orogenic segments, however, are different: in the Western Carpathians, the Moho is a flat surface; in the Dinarides, a medium Moho root is observed; the Southern Carpathians are characterized by a thick crustal root. The differences are explained with the presence or absence of "subductible" oceanic crust along the Carpathians during the extrusion of Pannonian blocks. © Springer-Verlag 2005.
Keywords: CARPATHIANS; CRUSTAL STRUCTURE; GRAVITY MODELLING; PANNONIAN BASIN; TEISSEYRE-TORNQUIST ZONE